Cathetocephalus badilloi n. sp. (Cestoda: Cathetocephalidea) from the spinner shark Carcharhinus brevipinna off the coast of Yucatan, Mexico - Itzel Nayely Badillo-Del Río; David Iván G. Hernández-Mena; Víctor M. Vidal-Martínez (International Journal for Parasitology: Parasites and Wildlife, 2023)
This study describes a new species belonging to the genus Cathetocephalus from the spinner shark Carcharhinus brevipinna off the coast of Yucatan, Mexico. Cathetocephalus badilloi n. sp. has a soft scolex transversely positioned to the long axis of the strobila. The scolex is composed of an apical pad, papillate band and rugose base. The papillate band has two papillary segments; the upper segment has numerous papillae, positioned one next to the other in an irregular and heterogeneous way with a spongy texture that remains along the band. The lower papillary segment has numerous papillae positioned one next to the other, without space between them. This papillary band presents flattened rectangular papillae with a division located at the top of each the papilla, giving it the appearance of a molar tooth. Using the 28S rDNA gene and the method of Maximum Likelihood (ML) for phylogenetic analysis, we identified the present material as a new species. We did not collect specimens with mature or gravid proglottids, but since the specific identification of the members of this genus is based on the characteristics of the scolex, our proposal of the new species is determined by the morphology of this organ as well as the molecular results obtained.